Internalisasi Pendidikan Karakter Dalam Budaya MA Raden Rahmat Seloreji, Mojowarno, Jombang - Abidin, Mohammad Khoirul; Pane, Rohani Sitorus; Wijdan, Muhammad Hibban; Lessy, Zulkipli (Arfannur, 2023)
Internalization is the unification of attitudes, opinions, and behavior in personality. The purpose of the study was to explore the process of internalizing character education in madrasa culture at MA Raden Rahmat to determine the process of internalizing character education through madrasa culture. The study used a qualitative approach with research design using interviews and direct observation. The results of the research include: character building carried out through madrasa culture to form students who are honest, disciplined, responsible, caring, polite, environmentally friendly, mutual cooperation, cooperation, peace-loving, responsive and pro-active; Madrasa culture at MA Raden Rahmat includes: praying dhuha and dhuhur in congregation, istighasah and tahlil, reading certain surahs of the Qur’an, working with coins, morning apples, fashion crafts. Meanwhile results also showed supporting factors such as good examples are reflected by the teachers, and get appreciation from the community. Whereas the inhibiting factors are the lack of adequate facilities, differences of opinion and views between teachers and students, the psychological condition of children, and the lack of cooperation between teachers and parents. ABSTRAK Internalisasi merupakan penyatuan sikap, pendapat, tingkah laku dalam kepribadian. Tujuan penelitian ini adalah untuk menggali proses internalisasi pendidikan karakter dalam budaya madrasah di MA Raden Rahmat Selorejo, Mojowarno, Jombang untuk mengetahui proses internalisasi pendidikan karakter melalui budaya madrasah. Penelitian ini menggunakan pendekatan kualitatif dengan desainnya menggunakan metode wawancara dan observasi secara langsung. Hasilnya menunjukkan bahwa penanaman karakter yang dilakukan melalui budaya madrasah untuk membentuk siswa yang jujur, disiplin, tanggungjawab, peduli, santun, ramah lingkungan, gotong royong, kerja sama, cinta damai, responsif dan pro-aktif; budaya madrasah di MA Raden Rahmat antara lain: shalat dhuha dan dhuhur berjamaah, istighasah dan tahlil, membaca surat-surat tertentu, giat koin, apel pagi, dan prakarya tata busana. Namun dalam praktek ini terdapat faktor pendukung seperti keteladanan yang baik dicerminkan oleh para guru, dan mendapat apresiasi dari masyarakat. Adapun faktor penghambat yakni kurangnya fasilitas yang memadai, perbedaan pendapat dan pandangan antar guru dan siswa, kondisi psikologis anak, dan kurangnya kerjasama antarguru dan orang tua. Kata kunci: Internalisasi, Pendidikan Karakter, Budaya Madrasah